U.S. monetary policy and financial markets - Meek, Paul.; Federal Reserve Bank of New York. (New York, NY (33 Liberty St., New York 10045) : Federal Reserve Bank of New York, 1982)
This volume focuses on the crucial relationships between domestic and international economic developments and on their implications for monetary, fiscal, and exchange rate policies.
aia 28/01/2019
Loans
Keywords: Monetary policy; Money market